New Approach for Lactose Transglycosylation into Galactooligosaccharides - Gorlov, Ivan Fiodorovich; Khramtsov, Andrey Georgievich; Evdokimov, Ivan Alekseevich; Lodygin, Aleksey Dmitrievich; Rodnaya, Anastasia Borisovna; Slozhenkina, Marina Ivanovna; Mosolova, Natalia Ivanovna; Zlobina, Elena Yurievna; Karpenko, Ekaterina Vladimirovna (Pakistan Journal of Nutrition, 2015)
The purpose of the research was to explore the feasibility of enzymatic catalysis with elements of microbial synthesis of the polymerization of lactose monomers into the galactooligosaccharides (GalOS) nanoclusters. The main objects of the study were the lactose solution (milk raw sugar) and the whey permeates subjected to electroactivation and fermentation by Lactokanestsin G20x and Ha-Lactase. To determine the carbohydrate composition of samples and finished products, the high-pressure liquid chromatography method was used. For the process monitoring, the freezing point depression method and the lactose transformation rate were applied. The directed and controlled types of synthesis of a universal agricultural bioecologic raw material of animal origin were examined in the context of solving a task of transglycosylation of the whey lactose into the GalOS. A biotechnology paradigm of the enzyme-catalyzed GalOS polymerization by [beta]-galactosidase in model solutions of milk sugar and industrial samples of the whey permeates was substantiated. The transglycosylation patterns with optimized parameters of the GalOS synthesis were established. The GalOS synthesis in the whey permeate had an optimum, which was observed at a temperature of (50±2)°C and a pH value of (6.4±0.2). On the basis of the research results, the Innovative Technology Platform (the priority was patented with know-how elements) of the GalOS-concentrates production was generated. The relevance of this work is due not only to the practical applicability of the GalOS-concentrates as prebiotic components and their biological value, but also to the need for the complex processing of lactose containing raw material.